Simulation analysis of paddling motions in a single kayak: Development of a comprehensive dynamic model of a paddler, paddle and hull - Nakashima, M.; Yamazaki, S.; Yue, J.; Nakagaki, K. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2014)
The objective of this study was to develop a comprehensive dynamic model of the paddler, paddle and hull for a simulation analysis of the paddling motion in a single kayak. In the development of the model, a similar simulation model, not for the kayak, but for human swimming, was utilized. The paddler was represented as a series of 21 truncated elliptic cones. The paddle was represented as three truncated elliptic cones for the two blades and shaft. For the hull, an extension of the original simulation model to represent the detailed three-dimensional hull shape was carried out. In the extended hull model, the thin elliptic plate was replaced by a plate with a detailed cross-sectional shape. The paddler, paddle and hull in the model were connected by means of virtual springs and dampers. The geometries of the paddler, paddle and hull were acquired based on the experiments that measured them. The joint motion of the paddler was measured by means of motion analysis as well. By inputting the acquired data, simulation of the paddling motion was conducted. From the results, it was confirmed that the joint motion acquired in the experiment was successfully input into the simulation. It was also confirmed that the paddler, paddle and the hull were successfully connected by the virtual springs and dampers. In the simulation, the averaged velocity of the hull in the propulsive direction was 3.40 m/s, which was 11% lower than the actual value of 3.8 m/s.